2018
DOI: 10.1002/hyp.13293
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and snowmelt drivers of a marginal subalpine snowpack

Abstract: Snowmelt from the seasonal snowpack in the Australian Alps is a significant source of water for irrigated agriculture, electricity generation, and environmental flows in the Murray–Darling Basin. Previous studies have reported negative decadal to multidecadal trends in maximum snow depth, snow season duration, and snow‐covered area. Here, we characterise the energy balance of this marginal maritime snowpack for the first time. Turbulent fluxes measured using the eddy covariance and bulk aerodynamic methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 88 publications
(155 reference statements)
5
24
0
Order By: Relevance
“…Temperatures between 0.4 and 1.8°C, conducive to mixed‐phase precipitation according to Chubb et al (), accounted for 27% (223 mm) of the May–October precipitation in 2015 but only 14% (275 mm) in 2016. With respect to ablation, air temperature is related to not only the sensible heat flux but also incoming longwave radiation (Ohmura, ), which Bilish et al () found to be the dominant source of energy to the snowpack at Pipers Creek.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperatures between 0.4 and 1.8°C, conducive to mixed‐phase precipitation according to Chubb et al (), accounted for 27% (223 mm) of the May–October precipitation in 2015 but only 14% (275 mm) in 2016. With respect to ablation, air temperature is related to not only the sensible heat flux but also incoming longwave radiation (Ohmura, ), which Bilish et al () found to be the dominant source of energy to the snowpack at Pipers Creek.…”
Section: Discussionmentioning
confidence: 99%
“…These include high bulk densities and low vertical temperature gradients. Bilish et al () suggested that the Australian snowpack may have some relevance to understanding snowpack behaviour in the more marginal of global snow regions when no local long‐term measurements exist.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations